A League is born: the League of Ireland's inaugural season, 1921-1922. (17th November 2021) - Heffernan, Conor; Taylor, Joseph
ABSTRACT: The 1921–1922 football season saw the creation of the League of Ireland. Envisioned as an all-Ireland competition, the League was posited as a new wide sweeping competition which would help to unite the various football leagues around Ireland. Born at a time of considerable social and political unrest, the League of Ireland was warmly received by football fans and journalists. Shedding light on a previously underexplored part of the League's history, the following study tracks the difficulties and popularity of the League's inaugural season. In doing so, it is argued that the League was highly dependent on media coverage of the season, which attempted to keep public interest in the games at a time when broader political and economic problems threatened to stop the League's progress. The League's survival was, in many ways, predicated on its relationship with the media.